1988
DOI: 10.1002/ardp.19883210803
|View full text |Cite
|
Sign up to set email alerts
|

Lactone, 18. Mitt. Synthese lactonverbrückter 1,1‐Diarylpropylamine

Abstract: durchAddition von Aminen an die &4roylaciylsauren 1-4 und anschlieDende Umsetzung von 5a-h mit Phenyllithium schlieljt die Lucke in der homologen Reihe lactonverbriickter Diarylalkylamine2-5).Synthesis of the 3~amino~5,5-diaryl~4,5~di~ydro~2~3N~~furanones 6a-h by addition of amines to the P-aroylacrylic acids 1-4 and treatment of 5a-h with phenyllithium closes the gap in the homologous series of y-lactonized diarylalkanamines2-s).uber die Darstellung y-lactonjsierter Diarylethyl-2), -b~t y l -~,~) und -pentyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…We found that the reactions of hydrazine hydrate with pyrrolidine and piperidine adducts of β (p toluyl)acrylic acid (9, 10) 16 occurs in a different way: elimination of the amine precedes cyclization to give 3 (p tolyl)pyrazoline 5 carboxylic acid (11) The precipitate that did not dissolve in KOH was filtered off, washed with water, dried in vacuo, and refluxed in CHCl 3 for purification to give methyl α Reaction of methyl β β β β β (p toluyl)acrylate with NH 2 OH•HCl. Aqueous NH 2 OH•HCl (8.34 g, 0.12 mol) was added to a satu rated solution of methyl β (p toluyl)acrylate (2.04 g, 0.01 mol) in MeOH.…”
Section: Methodsmentioning
confidence: 99%
“…We found that the reactions of hydrazine hydrate with pyrrolidine and piperidine adducts of β (p toluyl)acrylic acid (9, 10) 16 occurs in a different way: elimination of the amine precedes cyclization to give 3 (p tolyl)pyrazoline 5 carboxylic acid (11) The precipitate that did not dissolve in KOH was filtered off, washed with water, dried in vacuo, and refluxed in CHCl 3 for purification to give methyl α Reaction of methyl β β β β β (p toluyl)acrylate with NH 2 OH•HCl. Aqueous NH 2 OH•HCl (8.34 g, 0.12 mol) was added to a satu rated solution of methyl β (p toluyl)acrylate (2.04 g, 0.01 mol) in MeOH.…”
Section: Methodsmentioning
confidence: 99%